Manufacturing method of drawing pin micro-nano robot
By adding a hole-mounted base on the tubular micro-nano robot to form a thumbtack micro-nano robot, it is prepared by electrochemical deposition method, and the problem of single structure of the tubular micro-nano robot is solved, achieving structural diversity and research expansion.
Patent Information
- Application Number
- CN202510079649.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-18
AI Technical Summary
The prior art has conducted few research on the appearance improvement of tubular micro-nano robots, which has limited the comparative analysis of tubular micro-nano robots of different forms.
A layer of holes is added to the tubular micro-nano robot to form a "thumb-pin" micro-nano robot, which is prepared by template-assisted electrodeposition method and electrochemical deposition method to control the deposition current intensity and time to prepare micro-nano robots with controllable base size.
The problem of single structure of tubular micro-nano robots is solved, the structural asymmetry is increased, and the possibility of research on micro-nano robots of different forms is expanded.
Smart Images

Figure CN119824496A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of micro-nano robots, and in particular to a method for preparing a pushpin micro-nano robot. Background Art
[0002] Micro-nano robots have been a hot topic and direction of international academic research in recent years, showing great potential in the fields of environmental remediation, biomedical engineering, cargo transportation, etc. Micro-nano robots are robots between micrometer and nanometer scales that can convert external energy into mechanical energy for their own movement. They have the advantages of small size, large thrust-to-weight ratio, good controllability, and strong expandability. Compared with micro-nano robots of other shapes, tubular micro-nano robots have excellent motion performance and strong load capacity. However, the current research on tubular micro-nano robots mainly focuses on modifying their tubular outer or inner layers, and there is less research on appearance improvement, which limits the comparative analysis of tubular micro-nano robots of different forms. In view of this, a preparation method of a "thumbnail" micro-nano robot is provided. The micro-nano robot adds a layer of base with holes on the basis of the tubular micro-nano robot, increases the asymmetry of the tubular micro-nano robot structure, and solves the problem of the single structure of the tubular micro-nano robot. It is of great significance for further research on tubular micro-nano robots. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a pushpin micro-nano robot, which has the beneficial effect of solving the problem of the single structure of the tubular micro-nano robot.
[0004] A method for preparing a pushpin micro-nano robot comprises the following steps:
[0005] S1: Obtain a porous polycarbonate (PC) template;
[0006] S2: using a magnetron sputtering deposition system to ionize argon gas and bombard the silver target with ions under the action of an electric field, sputtering silver atoms to the reverse side of the porous polycarbonate template;
[0007] S3: Paste the double-conductor copper foil tape to one side of the porous polycarbonate template with silver to ensure good electrical contact with the silver side of the porous polycarbonate template;
[0008] S4: The pushpin micro-nano robot was obtained by electrochemical deposition;
[0009] S5: removing the template from the electrochemical deposition device, washing the template surface with deionized water, and removing the electrolyte;
[0010] S6: polish the silver surface of the polycarbonate template using alumina slurry to remove the surface silver layer, and place the template in a centrifuge tube;
[0011] S7: Add dichloromethane solution to the centrifuge tube to soak the template, and use an ultrasonic cleaner to allow the template to fully react with dichloromethane to dissolve the polycarbonate. Put the centrifuge tube into a centrifuge at a centrifuge speed of 6000 rpm for 3 minutes, collect the thumbtack micro-nano robot, and repeat the above operation 3 times;
[0012] S8: After cleaning the thumbtack micro-nano robot three times with ethanol and deionized water respectively, store it in deionized water at room temperature.
[0013] Furthermore, the electrochemical deposition adopts a three-electrode system, including a working electrode for depositing nickel and gold, a reference electrode for measuring the electrode potential, and a counter electrode for providing a polarization current loop, with silver chloride as the reference electrode, a platinum wire as the counter electrode, and a silver-surface porous polycarbonate template as the working electrode. A gold plating solution and a nickel plating solution are used as electrolytes, respectively. The plating solution is composed of a main salt, a complexing agent, a buffer, etc., wherein the main salt of the gold plating solution is 0.04 mol / L tetrahydrate chloroauric acid, the complexing agent is 0.56 mol / L sodium sulfite, 0.26 mol / L potassium citrate, 0.14 mol / L ethylenediaminetetraacetic acid, the buffer is 10 mol / L sodium hydroxide, and the conductive salt is 0.81 mol / L potassium chloride.
[0014] Furthermore, when nickel is deposited first and then gold is deposited during the electrochemical deposition, the main body of the thumbtack is deposited first and is made of nickel. The base part is deposited later and is made of gold. A two-step current method is used in the electrochemical deposition of nickel. In the first step, the current is -20mA and the deposition time is 0.1s. In the second step, the current is -6mA and the deposition time is 1000s. After the nickel deposition is completed, the porous polycarbonate template is rinsed with deionized water to remove the surface electrolyte and replace the new electrolyte with a gold plating solution. In the electrochemical deposition of gold, a constant current method is used to deposit gold, the cathode current is 4mA, and the deposition time is 100s, to obtain a thumbtack micro-nano robot with an outer tube diameter of 4.35±0.076um, a wall thickness of 1.64±0.121um, a tube length of 9.95±0.681um, a base diameter of 9.40±0.660um, and a base thickness of 2.91±0.624um.
[0015] Furthermore, by taking a new template and changing the deposition time or current intensity, a thumbtack micro-nano robot with controllable base size can be prepared.
[0016] Furthermore, when the duration of electrochemical gold deposition was changed to 200 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 9.88±0.379 um and a base thickness of 2.75±0.065 um was obtained.
[0017] Furthermore, when the duration of electrochemical gold deposition was changed to 50 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 7.23±0.335 um and a base thickness of 1.49±0.096 um was obtained.
[0018] Furthermore, the cathode current of electrochemically deposited gold was changed to 3 mA, and the other parameters remained unchanged, resulting in a thumbtack micro-nano robot with a base diameter of 8.98±1.066 um and a base thickness of 2.36±0.511 um.
[0019] Furthermore, the cathode current of electrochemically deposited gold was changed to 2 mA, and the other parameters remained unchanged, resulting in a thumbtack micro-nano robot with a base diameter of 8.06±0.309 um and a base thickness of 1.87±0.374 um.
[0020] Furthermore, a new template was taken and the deposition order was changed, with gold deposited first and nickel deposited later, to obtain a thumbtack micro-nano robot with a main body made of nickel and gold and a base material containing a small amount of gold and a large amount of nickel, wherein the base diameter was 8.84±0.958um and the base thickness was 1.82±0.564um.
[0021] Furthermore, the diameter of the porous polycarbonate template in S1 is 25 mm, and the pore diameter is 5 um; and the sputtering thickness of silver atoms sputtered onto the reverse side of the porous polycarbonate template in S2 is 200 nm.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention adopts a template-assisted electrodeposition method, which can manufacture a large number of pushpin micro-nano robots without complex manufacturing requirements.
[0024] 2. The present invention utilizes electrochemical deposition to first deposit metal that is easy to be the tubular body of the thumbtack, and then deposit metal that is easy to be the base part of the thumbtack. By changing the deposition order, a thumbtack micro-nano robot with different metals as the tubular body and the base body can be prepared.
[0025] 3. The present invention utilizes electrochemical deposition to control the metal deposition rate and deposition thickness by controlling the deposition current intensity and deposition time, thereby being able to prepare a thumbtack micro-nano robot with a controllable base size. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0027] Figure 1 Schematic diagram of an electrochemical deposition device;
[0028] Figure 2 The SEM and EDS diagrams of the pushpin micro-nano robot;
[0029] Figure 3 SEM images of micro-nano robots with different sizes of bases under different deposition parameters;
[0030] In the figure: working electrode 1; reference electrode 2; counter electrode 3; reaction vessel base 4; sealing ring 5; reaction vessel 6; anode 7; electrochemical workstation 8; double-conducting copper foil tape 9. DETAILED DESCRIPTION
[0031] A method for preparing a pushpin micro-nano robot comprises the following steps:
[0032] S1: Obtain a porous polycarbonate (PC) template;
[0033] S2: using a magnetron sputtering deposition system to ionize argon gas and bombard the silver target with ions under the action of an electric field, sputtering silver atoms to the reverse side of the porous polycarbonate template;
[0034] S3: Paste the double-conductor copper foil tape to one side of the porous polycarbonate template with silver to ensure good electrical contact with the silver side of the porous polycarbonate template;
[0035] S4: The pushpin micro-nano robot was obtained by electrochemical deposition;
[0036] S5: removing the template from the electrochemical deposition device, washing the template surface with deionized water, and removing the electrolyte;
[0037] S6: polish the silver surface of the polycarbonate template using alumina slurry to remove the surface silver layer, and place the template in a centrifuge tube;
[0038] S7: Add dichloromethane solution to the centrifuge tube to soak the template, and use an ultrasonic cleaner to allow the template to fully react with dichloromethane to dissolve the polycarbonate. Put the centrifuge tube into a centrifuge at a centrifuge speed of 6000 rpm for 3 minutes, collect the thumbtack micro-nano robot, and repeat the above operation 3 times;
[0039] S8: After cleaning the thumbtack micro-nano robot three times with ethanol and deionized water respectively, store it in deionized water at room temperature.
[0040] The electrochemical deposition method uses an electrochemical deposition device, such as Figure 1As shown, the electrochemical deposition device includes a working electrode 1, a reference electrode 2, a counter electrode 3, a reaction vessel base 4, a sealing ring 5, a reaction vessel 6, an anode 7 and an electrochemical workstation 8, and a double-conducting copper foil tape 9. The working electrode 1 is arranged on the upper side of the double-conducting copper foil tape 9, and the double-conducting copper foil tape 9 is arranged on the upper side of the reaction vessel base 4. A sealing ring 5 is arranged between the working electrode 1 and the reaction vessel 6. The double-conducting copper foil tape 9 is connected to the electrochemical workstation 8 through the anode 7. The reference electrode 2 and the counter electrode 3 are connected to the electrochemical workstation 8. The reference electrode 2 and the counter electrode 3 extend into the reaction vessel 6. The electrochemical deposition adopts a three-electrode system, including deposition of nickel and gold. The working electrode 1, the reference electrode 2 for measuring the electrode potential, the counter electrode 3 for providing the polarization current loop, the silver chloride 2 as the reference electrode, the platinum wire as the counter electrode 3, the silver-surfaced porous polycarbonate template as the working electrode 1, the gold plating solution and the nickel plating solution as the electrolyte, respectively, the plating solution is composed of a main salt, a complexing agent, and a buffering agent, wherein the main salt of the gold plating solution is 0.04 mol / L tetrahydrate chloroauric acid, the complexing agent is 0.56 mol / L sodium sulfite, 0.26 mol / L potassium citrate, 0.14 mol / L ethylenediaminetetraacetic acid, the buffer is 10 mol / L sodium hydroxide, and the conductive salt is 0.81 mol / L potassium chloride. After adding sodium sulfite, the main salt is mainly [Au(SO3)2] 3- Potassium citrate and EDTA have good chelating effect and can be bound to [Au(SO3)2] 3- Nearby, it is conducive to the precipitation of gold ions. When pH <7, [Au(SO3)2] 3- Dissociation into Au + and SO3 2- , then Au + Deposition by disproportionation reaction, SO3 2- Decomposition generates SO2, which reduces the stability of the gold plating solution. Therefore, the pH value of the above solution is adjusted to 8-10 with 10 mol / L sodium hydroxide solution. 3- +2OH-→2Au↓+SO4 2- +H2O+3SO3 2- The nickel plating solution contains 1.6 mol / L nickel tetrahydrate sulfamate as the main salt and 0.32 mol / L boric acid as the pH buffer to enhance the electroplating effect. 0.08 mol / L nickel chloride hexahydrate is added to prevent anode passivation and increase the number of free ions in the solution to enhance conductivity.
[0041] When nickel is deposited first and gold is deposited later during the electrochemical deposition, the main body of the thumbtack is deposited first and is made of nickel, and the base part is deposited later and is made of gold. A two-step current method is used in the process of electrochemical nickel deposition. In the first step, the current is -20mA and the deposition time is 0.1s. In the second step, the current is -6mA and the deposition time is 1000s. After the nickel deposition is completed, the porous polycarbonate template is rinsed with deionized water to remove the surface electrolyte and replace the new electrolyte with a gold plating solution. In the process of electrochemical gold deposition, a constant current method is used to deposit gold, the cathode current is 4mA, and the deposition time is 100s, so as to obtain a thumbtack micro-nano robot with an outer tube diameter of 4.35±0.076um, a wall thickness of 1.64±0.121um, a tube diameter length of 9.95±0.681um, a base diameter of 9.40±0.660um, and a base thickness of 2.91±0.624um.
[0042] Take a new template, change the deposition time or current intensity, and prepare a thumbtack micro-nano robot with controllable base size.
[0043] When the duration of electrochemical gold deposition was changed to 200 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 9.88±0.379 um and a base thickness of 2.75±0.065 um was obtained.
[0044] When the duration of electrochemical gold deposition was changed to 50 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 7.23±0.335 um and a base thickness of 1.49±0.096 um was obtained.
[0045] The cathode current of electrochemically deposited gold was changed to 3 mA, and the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 8.98±1.066um and a base thickness of 2.36±0.511um was obtained.
[0046] The cathode current of electrochemically deposited gold was changed to 2 mA, and the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 8.06±0.309 um and a base thickness of 1.87±0.374 um was obtained.
[0047] Take a new template and change the deposition order, depositing gold first and then nickel, to obtain a thumbtack micro-nano robot with a main body made of nickel and gold and a base material containing a small amount of gold and a large amount of nickel, wherein the base diameter is 8.84±0.958um and the base thickness is 1.82±0.564um.
[0048] The diameter of the porous polycarbonate template in S1 is 25 mm, and the pore diameter is 5 um; in S2, the sputtering thickness of silver atoms sputtered onto the reverse side of the porous polycarbonate template is 200 nm.
Claims
1. A method for preparing a pushpin micro-nano robot, characterized in that: The following steps are involved: S1: Obtain a porous polycarbonate (PC) template; S2: using a magnetron sputtering deposition system to ionize argon gas and bombard the silver target with ions under the action of an electric field, sputtering silver atoms to the reverse side of the porous polycarbonate template; S3: Paste the double-conductor copper foil tape to one side of the porous polycarbonate template with silver to ensure good electrical contact with the silver side of the porous polycarbonate template; S4: The pushpin micro-nano robot was obtained by electrochemical deposition; S5: removing the template from the electrochemical deposition device, washing the template surface with deionized water, and removing the electrolyte; S6: polish the silver surface of the polycarbonate template using alumina slurry to remove the surface silver layer, and place the template in a centrifuge tube; S7: Add dichloromethane solution to the centrifuge tube to soak the template, and use an ultrasonic cleaner to allow the template to fully react with dichloromethane to dissolve the polycarbonate. Put the centrifuge tube into a centrifuge at a centrifuge speed of 6000 rpm for 3 minutes, collect the thumbtack micro-nano robot, and repeat the above operation 3 times; S8: After cleaning the thumbtack micro-nano robot three times with ethanol and deionized water respectively, store it in deionized water at room temperature.
2. The method for preparing a pushpin micro-nano robot according to claim 1, characterized in that: The electrochemical deposition adopts a three-electrode system, including a working electrode for depositing nickel and gold, a reference electrode for measuring the electrode potential, and a counter electrode for providing a polarization current loop. Silver chloride is used as the reference electrode, a platinum wire is used as the counter electrode, and a silver-surface porous polycarbonate template is used as the working electrode. A gold plating solution and a nickel plating solution are used as electrolytes, respectively. The plating solution is composed of a main salt, a complexing agent, a buffer, and the like. The main salt of the gold plating solution is 0.04 mol / L tetrahydrate chloroauric acid, the complexing agent is 0.56 mol / L sodium sulfite, 0.26 mol / L potassium citrate, and 0.14 mol / L ethylenediaminetetraacetic acid. The buffer is 10 mol / L sodium hydroxide, and the conductive salt is 0.81 mol / L potassium chloride.
3. The method for preparing a pushpin micro-nano robot according to claim 2, characterized in that: When nickel is deposited first and gold is deposited later during the electrochemical deposition, the main body of the thumbtack is deposited first and is made of nickel, and the base part is deposited later and is made of gold. A two-step current method is used in the process of electrochemical nickel deposition. In the first step, the current is -20mA and the deposition time is 0.1s. In the second step, the current is -6mA and the deposition time is 1000s. After the nickel deposition is completed, the porous polycarbonate template is rinsed with deionized water to remove the surface electrolyte and replace the new electrolyte with a gold plating solution. In the process of electrochemical gold deposition, a constant current method is used to deposit gold, the cathode current is 4mA, and the deposition time is 100s, so as to obtain a thumbtack micro-nano robot with an outer tube diameter of 4.35±0.076um, a wall thickness of 1.64±0.121um, a tube diameter length of 9.95±0.681um, a base diameter of 9.40±0.660um, and a base thickness of 2.91±0.624um.
4. The method for preparing a pushpin micro-nano robot according to claim 3, characterized in that: Take a new template, change the deposition time or current intensity, and prepare a thumbtack micro-nano robot with controllable base size.
5. The method for preparing a pushpin micro-nano robot according to claim 4, characterized in that: When the duration of electrochemical gold deposition was changed to 200 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 9.88±0.379 um and a base thickness of 2.75±0.065 um was obtained.
6. The method for preparing a pushpin micro-nano robot according to claim 4, characterized in that: When the duration of electrochemical gold deposition was changed to 50 s, the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 7.23±0.335 um and a base thickness of 1.49±0.096 um was obtained.
7. The method for preparing a pushpin micro-nano robot according to claim 4, characterized in that: The cathode current of electrochemically deposited gold was changed to 3 mA, and the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 8.98±1.066um and a base thickness of 2.36±0.511um was obtained.
8. The method for preparing a pushpin micro-nano robot according to claim 4, characterized in that: The cathode current of electrochemically deposited gold was changed to 2 mA, and the other parameters remained unchanged, and a thumbtack micro-nano robot with a base diameter of 8.06±0.309 um and a base thickness of 1.87±0.374 um was obtained.
9. The method for preparing a pushpin micro-nano robot according to claim 3, characterized in that: Take a new template and change the deposition order, depositing gold first and then nickel, to obtain a thumbtack micro-nano robot with a main body made of nickel and gold and a base material containing a small amount of gold and a large amount of nickel, wherein the base diameter is 8.84±0.958um and the base thickness is 1.82±0.564um.
10. The method for preparing a pushpin micro-nano robot according to claim 1, characterized in that: The diameter of the porous polycarbonate template in S1 is 25 mm, and the pore diameter is 5 um; in S2, the sputtering thickness of silver atoms sputtered onto the reverse side of the porous polycarbonate template is 200 nm.
Citation Information
Patent Citations
Tubular protein blot catalytic magnetic micro-motor as well as preparation method and application of tubular protein blot catalytic magnetic micro-motor
CN104089940A
Preparation method for self-driven polyamino acid micro-nano motor
CN108051493A
Preparation method and application of tubular western blot zinc-based acid-driven magnetic micromotor
CN113588966A
Electroplating bath suitable for preparing micro-nano motor by template-assisted method and electroplating
CN113755932A
Graphene / manganese dioxide micro-nano motor and preparation and application thereof
CN114377651A